The effect of particle size distributions on dust storm attenuation prediction for microwave propagation - Elsheikh, Elfatih A. A.; Islam, Md. Rafiqul; Alam, A. H. M. Zahirul; Ismail, Ahmad Fadzil; Al-Khateeb, Khalid A. Saeed; Elabdin, Zain (2010)
Dust storm effect on microwave signal attenuation has attracted many researchers recently. Many prediction models have been developed in order to predict microwave signal attenuation during the dust storm. Most of the dust storm prediction models have ignored the variation of the particle size inside the dust storms. Therefore, their predicted results didn't reflect those have been measured. In this paper two of the dust prediction models have been investigated based on particle size statistical distributions (normal, exponential and lognormal). The proposed modification reflects the actual variation of the dust particle size distribution in these prediction models. The predicted attenuation based on lognormal particle size distribution have been compared with the measured data and found close agreement.